ANALISIS TERHADAP PERILAKU BERTRANSAKSI ONLINE PENGGUNA FACEBOOK COMMERCE - Sahfitri, Vivi (JURNAL ILMIAH MATRIK, 2016)
Abstract: The concept of electronic commerce is widely used todays society, or better known as e-commerce, information technology was born as globalization in economics. Social networking is one of the media of electronic commerce, which currently has a lot of users. The purpose of this study was to examine factors that influence e-commerce user on social networks, one of which is the facebook for online transactions. Data analysis performed in this study using multiple linear regression techniques to look at the variables that affect behavior variables commerce facebook users either partially or simultaneously. The results of this study are expected to provide empirical evidence about the factors that influence the behavior of users of facebook commerce in conducting online transactions. In addition the test results are also expected to give evidence about the dominant factors that influence user behavior in online transactions through social networking media. Keywords: Perception of Service Quality, Perceived Ease, Perceived Trust worthiness, User Behavior, Facebook Commerce, Online Transactions.